Synthetic α- and β-Ser-ADP-ribosylated peptides reveal α-Ser-ADPr as the native epimer - Voorneveld, J; Rack, J; Ahel, I; Overkleeft, H; van der Marel, G; Filippov, D (American Chemical Society, 2018)
A solid-phase methodology to synthesize oligopeptides, specifically incorporating serine residues linked to ADP-ribose (ADPr), is presented. Through the synthesis of both α- and β-anomers of the phosphoribosylated Fmoc-Ser building block and their usage in our modified solid-phase peptide synthesis protocol, both α- and β-ADPr peptides from a naturally Ser-ADPr containing H2B sequence were obtained. With these, and by digestion studies using the human glycohydrolase, ARH3 (hARH3), compelling evidence is obtained that the α-Ser-ADPr linkage comprises the naturally occurring configuration.